Loan Loss Provisioning Behaviour: A Case of Tanzania - Bhatia, Bhavit (2013)
This paper explores loan loss provisioning behaviour of banks in Tanzania to understand if it follows income smoothing, business cycle or capital management hypothesis. It also looks at the impact of efficiency on provisioning behaviour. Data from 26 banks over a 7 year period from 2009 to 2015 were used to calculate the estimates of efficiency through Stochastic Frontier Analysis. These values were then included in a loan loss provisioning model with other independent variables and observed through the General Method of Moments (GMM) estimator. The results showed that banks are overall efficient, with efficiency improving from 0.863 in 2009 to 1.126 in 2015. The second part of the paper showed that Tanzanian banks exhibited procyclicality and capital management hypothesis. While the lags were insignificant, efficiency was positive and significant. This shows the importance of including them in the paper and the misleading effects its omission could have.